TNFR2 and IL‐12 coactivation enables slanDCs to support NK‐cell function via membrane‐bound TNF‐α. Issue 12 (29th October 2014) - Tufa, Dejene M.; Chatterjee, Debanjana; Low, Hui Z.; Schmidt, Reinhold E.; Jacobs, Roland
Abstract : Human blood NK cells exert strong cytotoxicity against transformed cells and produce different cytokines and chemokines with an important role in modulating immune responses. However, the nature of NK‐cell function depends on NK‐cell interaction with other immune cells. One type of immune cells that communicate with NK cells are 6‐sulfo LacNAc DCs (slanDCs), which comprise a major subpopulation of proinflammatory human blood DCs. In this study, we investigated the molecular mechanisms by which slanDCs interact with NK cells. Our in vitro studies demonstrate that LPS‐stimulated slanDCs enhance activation and function of NK cells essentially via membrane‐bound TNF‐α (mTNF‐α). LPS stimulation upregulates expression of mTNF‐α in slanDCs, and surface TNF receptor 2 (TNFR2) is upregulated on NK cells after coincubation with slanDCs. IL‐12 secreted by slanDCs increases surface expression of TNFR2 in NK cells. TNFR2 signaling in NK cells leads to activation of NF‐kB, a transcription factor for cytokines such as GM‐CSF. GM‐CSF provided by NK cells is responsible for enhancing IL‐12 secretion in slanDCs. In conclusion, TNFR2 and IL‐12 signaling, which support one another, enables slanDCs to enhance NK‐cell function through mTNF‐α, thereby regulating immune responses.